Peningkatan Kualitas Desain Kemasan dan Pengelolaan Data Usaha Pada Industri Rumah Tangga Kenko - I Gusti Ngurah Wikranta Arsa; I Made Bhaskara Gautama; I Made Mika Parwita; Putu Ricky Teddy Septian; I Made Arya Budhi Saputra (Indonesian Journal Publisher, 2022)
Kenk? is a home industry that produces organic almond milk. This business carries the theme of a healthy lifestyle and has a vision to participate in preserving the environment and nature. However, Kenk? still uses single-use plastic packaging to package its products. This is considered contradictory by its customers. In addition, business administration data which includes recording of production costs, turnover, sales transactions, and financial reports are still using notebooks. Therefore, this business has difficulty in making financial statements. This activity seeks and implements solutions to the partner's problems. The methods used in this activity include, among others, socialization, focus group discussions, providing packaging assistance and business management training. The packaging was replaced with glass bottles because it was considered more suitable for reuse and safe from harmful chemicals such as BPA. This activity also provides training on business administration data management using technology, namely MS Excel because it is considered capable of making financial reports easier. The results of this activity include the creation of new packaging in the form of BPA-free glass bottles and a new label design for the Kenk? home industry as well as the implementation of MS. Excel training activities to assist and simplify business administration management, as well as indirectly support the healthy lifestyle movement. and participate in preserving the environment and the natural surroundings. The follow-up activity planned for this partner is digital marketing and bringing their products to a digital platform, namely e-commerce.